Evaluasi Dampak Peningkatan Populasi Terhadap Ketersediaan Air Tanah pada Perumahan CitraGrand Kota Semarang - Desi Febrina Maharani; Dhiyan Krishna Wardhani; Lintang Jata Angghita (Praxis : Jurnal Sains, Teknologi, Masyarakat dan Jejaring, 2023)
Indonesia experiences an increase in population every year, which has an impact on the need for clean water. The increasing demand for clean water will certainly lead to the exploitation of water resources such as groundwater. Groundwater if used for a long period of time can potentially have a negative impact on both the environment and all living things and can affect the availability of water resources. One of the housing estates that still uses groundwater to meet the main needs of clean water is CitraGrand housing located on Jalan Kompol R. Soekanto, Tembalang District, Semarang City. This research was conducted in the CitraGrand residential area of Semarang City because this housing still uses groundwater along with the increasing population, so this research aims to analyze the distribution range and the amount of groundwater availability. Furthermore, the final results show that in 2033 the groundwater availability capacity in CitraGrand Semarang residential area has reached -3,936.9 million m3. This may indicate that the availability of groundwater can no longer be utilized as the main need for clean water. Therefore, the analysis results of this study can be used as a reference for developers related to strategies in sustainable water resources management.